Efecto del entrenamiento en ábaco mental sobre la flexibilidad cognitiva: Un estudio exploratorio - Giorgetti, Daniela; López-Navarro, Emilio; Munar, Enric (Revista de Investigacion en Educacion, 2021)
Mental Abacus (MA) training teaches students to solve math problems by visualizing a physical abacus structure to perform arithmetic operations. Research shows that MA practice relates with enhanced working memory in children, but other cognitive processes that could mediate the benefits registered remain unknown. The aim of the study was to analyze the effect of MA training in a cognitive flexibility task in twelve-year-old children, and compare it with a control group. 121 children from the sixth course of primary education were recruited. 54 students received MA training added during the academic year, while the control group received normative arithmetic instruction. MA training was provided by UCMAS Mental Arithmetic Spain S.L. To assess cognitive flexibility, we used the Trail Making Test (TMT). Data analysis entailed parametric assumptions check and a one-way ANOVA between MA and control group. There were no differences between groups in age. There were statistical differences in TMT-A (Z=-5,78, p<,001, d=,67) and TMT-B scores (Z=-2,24, p=,021, d=,08). Our data suggest that MA enhances cognitive flexibility in children. MA is a promising tool teaching math which benefits go beyond arithmetic calculation.
Effects of mental abacus training over cognitive flexibility: An exploratory study
Mental Abacus (MA) training teaches students to solve math problems by visualizing a physical abacus structure to perform arithmetic operations. Research shows that MA practice relates with enhanced working memory in children, but other cognitive processes that could mediate the benefits registered remain unknown. The aim of the study was to analyze the effect of MA training in a cognitive flexibility task in twelve-year-old children, and compare it with a control group. 121 children from the sixth course of primary education were recruited. 54 students received MA training added during the academic year, while the control group received normative arithmetic instruction. MA training was provided by UCMAS Mental Arithmetic Spain S.L. To assess cognitive flexibility, we used the Trail Making Test (TMT). Data analysis entailed parametric assumptions check and a one-way ANOVA between MA and control group. There were no differences between groups in age. There were statistical differences in TMT-A (Z=-5,78, p<,001, d=,67) and TMT-B scores (Z=-2,24, p=,021, d=,08). Our data suggest that MA enhances cognitive flexibility in children. MA is a promising tool teaching math which benefits go beyond arithmetic calculation.
Keywords: ábaco mental; flexibilidad cognitiva; cálculo aritmético; arithmetic computation; cognitive flexibility; mental abacus; Scopus; Emerging